Space-level cable high temperature resistant jacket based on silicone composite

CN122917545APending Publication Date: 2026-10-16DEZHOU HANGXING INTELLIGENT EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611238728.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]目前,航天领域广泛应用的电缆高温防护材料主要包括:无机纤维编织套管、聚四氟乙烯及其复合带以及硅橡胶类防护套,其中无机纤维编织套管具有较好的耐高温性能,但存在纤维易脆化、柔韧性差、弯曲后易开裂、耐磨性不足等缺陷,且在复杂结构线束中的敷设适应性较差

Benefits of technology

本发明通过在碳纤维表面修饰具有树枝状结构的超支化高分子聚合物,制得碳纤维接枝复合料,一方面来说,由于高分子聚合物结构中含有不饱和烯基取代基,能够在硫化过程中与硅橡胶基体产生相互作用,从而实现与硅橡胶基体之间的分子链缠绕交织,而且高分子聚合物的树枝状结构能够产生毛细管作用,延伸至硅橡胶的各个区域,进而极大改善碳纤维与硅橡胶之间的界面结合性能,可有效减少应力集中,提升材料的整体强度,使防护套在承受外力载荷时不易损坏。另一方面来说,高分子聚合物结构中含有大量的酰亚胺结构,能够极大的提升硅橡胶的稳定性,使其在受热分解时需要吸收更多的热量,从而有效提升防护套的耐高温性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786790623908-000001
    Figure REF-OBJ-1786790623908-000001
Patent Text Reader

Abstract

The application belongs to the technical field of materials, and particularly relates to a high-temperature-resistant protective sleeve for aerospace-grade cables based on an organic silicon compound. The protective sleeve is prepared by mixing, extruding and vulcanizing a methyl vinyl silicone rubber as a base material and a carbon fiber grafted composite material as an auxiliary material. The carbon fiber grafted composite material is prepared by modifying the surface of carbon fibers with a hyperbranched polymer having a dendritic structure. The alkenyl substituent in the structure of the hyperbranched polymer can interact with the silicone rubber matrix during the vulcanization process, greatly improving the interfacial bonding performance between the carbon fibers and the silicone rubber and enhancing the overall strength of the material, so that the protective sleeve is not easily damaged when subjected to external force load. On the other hand, the hyperbranched polymer structure contains a large number of imide structures, which can greatly improve the high-temperature resistance of the protective sleeve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials technology, specifically relating to a high-temperature resistant protective sleeve for aerospace-grade cables based on an organosilicon composite. Background Technology

[0002] During launch, on-orbit operation, and atmospheric reentry, spacecraft cable systems must withstand extremely harsh environmental conditions, including high-temperature heat flux, instantaneous high-temperature shocks, vacuum environments, high-energy radiation, and intense thermal cycling. Cables, especially those in the rocket engine exhaust region, on the outer surface of the reentry capsule, and near the propulsion system, can operate at temperatures exceeding 800°C. Therefore, aerospace-grade cable sheaths must possess excellent high-temperature resistance, thermal insulation, flexibility, aging resistance, and adaptability to the space environment.

[0003] Currently, the high-temperature protection materials for cables widely used in the aerospace field mainly include: inorganic fiber braided sleeves, polytetrafluoroethylene (PTFE) and its composite tapes, and silicone rubber protective sleeves. Among them, inorganic fiber braided sleeves have good high-temperature resistance, but they suffer from defects such as fiber embrittlement, poor flexibility, easy cracking after bending, and insufficient abrasion resistance. Furthermore, their adaptability in complex cable harness structures is poor. While PTFE and its composite tapes possess excellent high and low temperature resistance and chemical stability, they are insufficient for long-term use in higher temperature environments. In contrast, silicone rubber has good flexibility, weather resistance, and high and low temperature resistance, and has received considerable attention in the field of cable protective sleeves in recent years. However, silicone rubber has a low high-temperature tolerance limit, and its strength performance is actually difficult to meet requirements. Therefore, this invention provides a silicone-based protective sleeve that can solve the problems existing in the prior art. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide an aerospace-grade high-temperature resistant protective sleeve for cables based on organosilicon composites.

[0005] A first aspect of the present invention provides an aerospace-grade high-temperature resistant protective sheath for cables based on an organosilicon compound, comprising the following raw materials measured in parts by weight: Methyl vinyl silicone rubber: 78-86 parts; Carbon fiber grafted composite: 2-6.5 parts; Vulcanizing agent: 1-2 parts; Vulcanization accelerator: 0.5-1.5 parts; Carbon black: 10-15 parts; Mica powder: 10-18 parts; Lubricant: 2-3 parts; Anti-aging agent: 0.5-1 part; Zinc oxide: 2-4 parts; The carbon fiber grafted composite is prepared by modifying the surface of carbon fibers with a hyperbranched polymer.

[0006] As a preferred embodiment of the present invention, the method for preparing the protective sleeve includes the following steps: Step 1: Weigh each raw material according to the specified weight proportions to complete the material preparation; Step 2: Add methyl vinyl silicone rubber, carbon fiber grafted composite, carbon black, mica powder, lubricant, antioxidant, and zinc oxide to a mixer and mix evenly to form a mixture. Transfer the mixture to an open mill, add vulcanizing agent and vulcanization accelerator, pass through a thin mill, sheet out, and then extrude it. Finally, perform vulcanization and shaping treatment.

[0007] As a preferred embodiment of the present invention, the method for preparing the carbon fiber grafted composite material includes the following steps: Step A: Add the oxidized carbon fiber to an ethanol aqueous solution, disperse it evenly by ultrasonication, then continue to add surface modifier, adjust the pH to 3-4, adjust the temperature to 70-75℃, keep it warm and stir for 4-8 hours, then stop heating, cool down and discharge the material. The collected crude product is purified to obtain modified carbon fiber. Step B: Disperse the modified carbon fiber in N,N-dimethylformamide, add a binder and glacial acetic acid to the resulting dispersion, after which nitrogen gas is introduced for protection, stir well, raise the temperature to 60-70℃, keep it at this temperature and stir for 2-4 hours, continue to add tris(2-aminoethyl)amine, after which adjust the temperature to 70-80℃, continue to keep it at this temperature for 8-16 hours, stop heating, wait for it to cool to room temperature, add sodium borohydride as a reducing agent, continue stirring for 2-4 hours, separate the solid material, wash and remove impurities, and vacuum dry to obtain the carbon fiber grafted composite material.

[0008] As a preferred embodiment of the present invention, in step A, the oxidation method of the carbon fiber specifically comprises: Carbon fibers are dispersed in concentrated nitric acid, heated, and refluxed at 80-100℃ for 1-3 hours. Heating is then stopped, the material is cooled and discharged, washed until neutral, and then vacuum dried.

[0009] As a preferred embodiment of the present invention, in step A, the surface modifier is 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane.

[0010] As a preferred embodiment of the present invention, in step B, the binder is prepared by the following method: 1,2,3,6-Tetrahydrophthalimide was added to tetrahydrofuran and stirred until homogeneous. Then, the composite catalyst was added. After the addition was complete, the mixture was stirred until a homogeneous solution was formed. Then, 5-bromoisophthalaldehyde was added to the solution. After the addition was complete, the temperature was adjusted to 30-40℃ and stirred for 4-6 hours. Water was then added to quench the reaction. The solution was then extracted with ethyl acetate. After washing and drying, the organic phase was filtered to obtain the crude product, which was then recrystallized to obtain the linker.

[0011] As a preferred embodiment of the present invention, the molar ratio of 1,2,3,6-tetrahydrophthalimide and 5-bromoisophthalaldehyde is 1:1.

[0012] As a preferred embodiment of the present invention, the composite catalyst is a mixture of potassium carbonate and tetrabutylammonium bromide in a mass ratio of 1:0.05-0.1.

[0013] As a preferred embodiment of the present invention, the mass ratio of the modified carbon fiber, the binder and the tris(2-aminoethyl)amine is 1:0.2-0.3:0.1-0.15.

[0014] It should be noted that in the above technical solution, carbon fibers are first oxidized with concentrated nitric acid to produce oxygen-containing functional groups such as hydroxyl groups on their surface. Then, a silane coupling agent is used as a surface modifier to modify the surface of the oxidized carbon fibers, enabling the carbon fiber surface to carry active amino functional groups, thus obtaining modified carbon fibers. Finally, using the active amino groups of the modified carbon fibers as initiation sites, and using a linker and tris(2-aminoethyl)amine as chain extenders, the active amino groups in their structures undergo continuous Schiff base reactions with the aldehyde substituents, thereby forming a dendritic polymer with a hyperbranched imide structure linked by Schiff bases on the carbon fiber surface. Finally, the Schiff bases are reduced by using sodium borohydride as a reducing agent to form secondary amino groups, thus obtaining a carbon fiber grafted composite material.

[0015] The linker is prepared by using 1,2,3,6-tetrahydrophthalimide and 5-bromoisophthalaldehyde as raw materials, and the imide and halogen substituents in their structures undergo a substitution reaction under the action of a composite catalyst.

[0016] As a preferred embodiment of the present invention, the vulcanizing agent is benzoyl peroxide; the vulcanization accelerator is tetramethylthiuram disulfide.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention prepares a carbon fiber grafted composite by modifying the surface of carbon fibers with a hyperbranched polymer having a dendritic structure. On one hand, the unsaturated alkenyl substituents in the polymer structure allow it to interact with the silicone rubber matrix during vulcanization, resulting in molecular chain entanglement and interweaving. Furthermore, the dendritic structure of the polymer creates capillary action, extending to various regions of the silicone rubber, thus significantly improving the interfacial bonding between the carbon fiber and silicone rubber. This effectively reduces stress concentration, enhances the overall strength of the material, and makes the protective sleeve less prone to damage under external loads. On the other hand, the polymer structure contains a large number of imide structures, which greatly improves the stability of the silicone rubber, requiring it to absorb more heat during thermal decomposition, thereby effectively improving the high-temperature resistance of the protective sleeve. Detailed Implementation

[0018] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0019] Example 1

[0020] This embodiment provides an aerospace-grade high-temperature resistant protective sleeve for cables based on an organosilicon composite, which is made from the following raw materials measured in parts by weight: Methyl vinyl silicone rubber: 78 parts; Carbon fiber grafted composite: 2 parts; Benzoyl peroxide: 1 part; Tetramethylthiuram disulfide: 0.55 parts; Carbon black: 10 parts; Mica powder: 10 parts; Zinc stearate: 2 parts; Antioxidant 4010NA: 0.5 parts; Zinc oxide: 2 parts; The method for preparing the protective sleeve includes the following steps: Step 1: Weigh each raw material according to the specified weight proportions to complete the material preparation; Step 2: Add methyl vinyl silicone rubber, carbon fiber grafted composite, carbon black, mica powder, zinc stearate, antioxidant 4010NA, and zinc oxide to a mixer and mix evenly to form a mixture. Transfer the mixture to an open mill and add benzoyl peroxide and tetramethylthiuram disulfide. Pass through a thin sheet, extrude it, and finally perform vulcanization and shaping treatment.

[0021] The preparation method of carbon fiber grafted composite includes the following steps: Step ①: Disperse 5g of carbon fiber in 150mL of concentrated nitric acid, turn on the heater, reflux at 90℃ for 2 hours, then stop the heater, cool down and discharge the material, wash until neutral, and then vacuum dry. Step 2: Add 3.5g of oxidized carbon fiber to an ethanol aqueous solution and ultrasonically disperse it evenly. Then add 0.6g of 3-aminopropyltrimethoxysilane, adjust the pH to 4, adjust the temperature to 70℃, and keep it heated and stirred for 6 hours. Then stop heating, cool down and discharge the material. The collected crude product is purified to obtain modified carbon fiber. Step ③: Add 0.4 g of 1,2,3,6-tetrahydrophthalimide to tetrahydrofuran, stir and mix well. Then add 1 g of potassium carbonate and 0.1 g of tetrabutylammonium bromide. After the addition is complete, stir until a homogeneous mixture is formed. Then add 0.56 g of 5-bromoisophthalaldehyde to the mixture. After the addition is complete, adjust the temperature to 40℃, stir for 6 hours, quench with water, and then extract with ethyl acetate. After washing and drying the organic phase, filter out the crude product, and then recrystallize to obtain the linker. Step 4: Disperse 1.6g of modified carbon fiber into N,N-dimethylformamide. Add 0.4g of binder and 0.1g of glacial acetic acid to the resulting dispersion. After the addition is complete, purge with nitrogen for protection. Stir until homogeneous, then raise the temperature to 65℃ and keep stirring for 3 hours. Continue to add tris(2-aminoethyl)amine. After the addition is complete, adjust the temperature to 75℃ and keep it at that temperature for 12 hours. Stop heating and allow it to cool to room temperature. Add sodium borohydride as a reducing agent and continue stirring for 3 hours. Separate the solid material, wash to remove impurities, and vacuum dry to obtain the carbon fiber grafted composite material.

[0022] Example 2

[0023] This embodiment provides an aerospace-grade high-temperature resistant protective sleeve for cables based on an organosilicon composite, which is made from the following raw materials measured in parts by weight: Methyl vinyl silicone rubber: 80 parts; Carbon fiber grafted composite: 6 parts; Benzoyl peroxide: 1.5 parts; Tetramethylthiuram disulfide: 1 part; Carbon black: 12 parts; Mica powder: 15 parts; Zinc stearate: 3 parts; Antioxidant 4010NA: 0.6 parts; Zinc oxide: 3 parts; The method for preparing the protective sleeve includes the following steps: Step 1: Weigh each raw material according to the specified weight proportions to complete the material preparation; Step 2: Add methyl vinyl silicone rubber, carbon fiber grafted composite, carbon black, mica powder, zinc stearate, antioxidant 4010NA, and zinc oxide to a mixer and mix evenly to form a mixture. Transfer the mixture to an open mill and add benzoyl peroxide and tetramethylthiuram disulfide. Pass through a thin sheet, extrude it, and finally perform vulcanization and shaping treatment.

[0024] The preparation method of the carbon fiber grafted composite is the same as that in Example 1.

[0025] Example 3

[0026] This embodiment provides an aerospace-grade high-temperature resistant protective sleeve for cables based on an organosilicon composite, which is made from the following raw materials measured in parts by weight: Methyl vinyl silicone rubber: 86 parts; Carbon fiber grafted composite: 6.5 parts; Benzoyl peroxide: 2 parts; Tetramethylthiuram disulfide: 1.5 parts; Carbon black: 15 parts; Mica powder: 18 parts; Zinc stearate: 3 parts; Anti-aging agent 4010NA: 1 part; Zinc oxide: 4 parts; The method for preparing the protective sleeve includes the following steps: Step 1: Weigh each raw material according to the specified weight proportions to complete the material preparation; Step 2: Add methyl vinyl silicone rubber, carbon fiber grafted composite, carbon black, mica powder, zinc stearate, antioxidant 4010NA, and zinc oxide to a mixer and mix evenly to form a mixture. Transfer the mixture to an open mill and add benzoyl peroxide and tetramethylthiuram disulfide. Pass through a thin sheet, extrude it, and finally perform vulcanization and shaping treatment.

[0027] The preparation method of the carbon fiber grafted composite is the same as that in Example 1.

[0028] Comparative Example 1 The difference between this comparative example and Example 2 is that the carbon fiber grafted composite material is replaced with unmodified carbon fiber, while all other aspects are the same.

[0029] Comparative Example 2 The difference between this comparative example and Example 2 is that the carbon fiber grafted composite material is removed; otherwise, they are the same.

[0030] The protective sleeves provided in the above embodiments and comparative examples were subjected to performance tests, and the test methods are as follows: (1) Tensile properties were tested according to standard GB / T 528-2009; (2) Thermogravimetric analysis was used to test the high temperature resistance. The test method was as follows: in a nitrogen atmosphere, the temperature was increased from room temperature to 800℃ at a rate of 10℃ / min, and the initial decomposition temperature was recorded.

[0031] The performance test data above are shown in Table 1.

[0032] Table 1 Performance Test Results

[0033] As can be seen from the above, the protective sleeve prepared in the embodiments of the present invention has good comprehensive performance. After replacing the carbon fiber grafted composite with unmodified carbon fiber, due to the interface problem, the carbon fiber can hardly exert its own effect and cannot play a good stress transfer effect, which leads to a significant reduction in the mechanical properties of the protective sleeve. Moreover, it loses the special structure of the polymer, which leads to a significant decrease in the high temperature resistance of the material.

[0034] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention, including the best mode, and also to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the present invention.

Claims

1. A high-temperature resistant protective sleeve for aerospace-grade cables based on an organosilicon composite, characterized in that, It is made from the following raw materials, measured in parts by weight: Methyl vinyl silicone rubber: 78-86 parts; Carbon fiber grafted composite: 2-6.5 parts; Vulcanizing agent: 1-2 parts; Vulcanization accelerator: 0.5-1.5 parts; Carbon black: 10-15 parts; Mica powder: 10-18 parts; Lubricant: 2-3 parts; Anti-aging agent: 0.5-1 part; Zinc oxide: 2-4 parts; The carbon fiber grafted composite is prepared by modifying the surface of carbon fibers with a hyperbranched polymer.

2. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 1, characterized in that, The method for preparing the protective sleeve includes the following steps: Step 1: Weigh each raw material according to the specified weight proportions to complete the material preparation; Step 2: Add methyl vinyl silicone rubber, carbon fiber grafted composite, carbon black, mica powder, lubricant, antioxidant, and zinc oxide to a mixer and mix evenly to form a mixture. Transfer the mixture to an open mill, add vulcanizing agent and vulcanization accelerator, pass through a thin mill, sheet out, and then extrude it. Finally, perform vulcanization and shaping treatment.

3. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 1, characterized in that, The preparation method of the carbon fiber grafted composite material includes the following steps: Step A: Add the oxidized carbon fiber to an ethanol aqueous solution, disperse it evenly by ultrasonication, then continue to add surface modifier, adjust the pH to 3-4, adjust the temperature to 70-75℃, keep it warm and stir for 4-8 hours, then stop heating, cool down and discharge the material. The collected crude product is purified to obtain modified carbon fiber. Step B: Disperse the modified carbon fiber in N,N-dimethylformamide, add the binder and glacial acetic acid to the formed dispersion, after the addition is complete, purge with nitrogen for protection, stir well, raise the temperature to 60-70℃, keep it at this temperature and stir for 2-4 hours, continue to add tris(2-aminoethyl)amine, after the addition is complete, adjust the temperature to 70-80℃, continue to keep it at this temperature for 8-16 hours, stop heating, wait for it to cool to room temperature, add the reducing agent sodium borohydride, continue to stir for 2-4 hours, separate the solid material, wash and remove impurities, and vacuum dry to obtain the carbon fiber grafted composite material.

4. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 3, characterized in that, In step A, the oxidation method of the carbon fiber is specifically as follows: Carbon fibers are dispersed in concentrated nitric acid, heated, and refluxed at 80-100℃ for 1-3 hours. Heating is then stopped, the material is cooled and discharged, washed until neutral, and then vacuum dried.

5. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 3, characterized in that, In step A, the surface modifier is 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane.

6. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 3, characterized in that, In step B, the binder is prepared using the following method: 1,2,3,6-Tetrahydrophthalimide was added to tetrahydrofuran and stirred until homogeneous. Then, the composite catalyst was added. After the addition was complete, the mixture was stirred until a homogeneous solution was formed. Then, 5-bromoisophthalaldehyde was added to the solution. After the addition was complete, the temperature was adjusted to 30-40℃ and stirred for 4-6 hours. Water was then added to quench the reaction. The solution was then extracted with ethyl acetate. After washing and drying, the organic phase was filtered to obtain the crude product, which was then recrystallized to obtain the linker.

7. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 6, characterized in that, The molar ratio of 1,2,3,6-tetrahydrophthalimide to 5-bromoisophthalaldehyde is 1:

1.

8. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 6, characterized in that, The composite catalyst is a mixture of potassium carbonate and tetrabutylammonium bromide in a mass ratio of 1:0.05-0.

1.

9. A high-temperature resistant protective sleeve for aerospace-grade cables based on an organosilicon composite according to claim 3, characterized in that, The mass ratio of the modified carbon fiber, the binder, and tris(2-aminoethyl)amine is 1:0.2-0.3:0.1-0.

15.

10. The aerospace-grade high-temperature protective sleeve for cables based on organosilicon composites according to claim 1, characterized in that, The vulcanizing agent is benzoyl peroxide; the vulcanization accelerator is tetramethylthiuram disulfide.